(untitled) (Revista do Centro de Estudos Portugueses, 2009)
São Francisco é considerado um dos primeiros autores da literatura italiana. A poesia religiosa, inaugurada por ele na Úmbria, mais tarde atravessará o território italiano com outros adeptos como Jacopone da Todi. A experiência franciscana é emblemática pelos valores propostos e pela idéia de recusa ali contida. Aspectos que a tornam atual no século XX, sendo recuperada e “transformada” por intelectuais como Pier Paolo Pasolini e José Saramago. San Francisco is considered one of the first authors in Italian Literature. The religious poetry, inaugurated by him in Umbria, later cross the italian territory with others adepts as Jacopone da Todi. The Franciscan experience is emblematic because of the proposed values and because of the idea of refusal contained in it. Aspects that made the all experience actual in the XX century, being recupered and “transformed” by intellectuals as Pier Paolo Pasolini and José Saramago.